2009
DOI: 10.4319/lo.2009.54.6.1883
|View full text |Cite
|
Sign up to set email alerts
|

Complementary UV protective compounds in zooplankton

Abstract: Zooplankton accumulate several groups of photoprotective compounds to shield against damaging ultraviolet radiation (UV). One of these groups, the carotenoids, makes the animals more conspicuous to visually hunting predators, whereas others, such as the mycosporine-like amino acids (MAAs) may not. The blend of photoprotective compounds is therefore important for the UV defense but also for the ability to escape predation through crypsis. Here we assess laboratory and field data from different latitudes to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 48 publications
2
74
0
1
Order By: Relevance
“…The MAA concentrations in copepods in the present study were in generally at the low end of this range, but showed high variation between 0.02 and 10 µg mg -1 , depending on species and site, perhaps because ponds are more heterogeneous habitats than the lakes that were studied by Hylander et al (2009b).…”
Section: Range Of Pigments and Maas In High-latitude Zooplanktonmentioning
confidence: 87%
See 2 more Smart Citations
“…The MAA concentrations in copepods in the present study were in generally at the low end of this range, but showed high variation between 0.02 and 10 µg mg -1 , depending on species and site, perhaps because ponds are more heterogeneous habitats than the lakes that were studied by Hylander et al (2009b).…”
Section: Range Of Pigments and Maas In High-latitude Zooplanktonmentioning
confidence: 87%
“…The distribution of this species was restricted to the DOC-poorest ponds that were <1 m in depth, and the species was, therefore, highly exposed to UV radiation. Recently, Hylander et al (2009b) reported a latitudinal pattern in copepod MAA concentration, with low concentrations in Subarctic and temperate copepods (1.0 and 1.4 µg mg -1 ) compared to dry-temperate copepods (up to 58 µg mg -1…”
Section: Range Of Pigments and Maas In High-latitude Zooplanktonmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results further support that the mechanism behind the detrimental UVR was organism death. However, the large C content per individual under UVR suggests the storage of lipids associated with carotenoid pigmentation (Hylander et al 2009), which may be interpreted as a tolerance mechanism against UVR-induced stress.…”
Section: Discussionmentioning
confidence: 99%
“…The red coloration of copepods is due to carotenoids, a large family of lipid-soluble pigments that are synthesized only in primary producers but may be either accumulated by zooplankton or biologically converted to other carotenoids, notably astaxanthin, which is the primary carotenoid among crustaceans (Matsuno 2001;Andersson et al 2003;Rhodes 2006). Astaxanthin is a powerful antioxidant (McNulty et al 2007) occurring both in free form and esterified with fatty acids or associated with proteins (Cheesman et al 1967;Matsuno 2001).In zooplankton, carotenoid accumulation is a highly variable trait that has been linked to photoprotection against ultraviolet radiation (UVR) in field studies comparing lakes with differential UVR exposure and in experimental studies (Hairston 1976;Moeller et al 2005;Hylander et al 2009;Rautio and Tartarotti 2010;Sommaruga 2010). The underlying mechanism ascribing astaxanthin photoprotection properties involves the quenching of singlet oxygen ( 1 O 2 ) produced during UVR exposure rather than direct absorption or reflectance of the hazardous wavelengths (Krinsky 1979;Kobayashi and Sakamoto 1999).…”
mentioning
confidence: 99%